2011
DOI: 10.1016/s0140-6736(11)60739-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lowering LDL cholesterol with simvastatin plus ezetimibe in patients with chronic kidney disease (Study of Heart and Renal Protection): a randomised placebo-controlled trial

Abstract: SummaryBackgroundLowering LDL cholesterol with statin regimens reduces the risk of myocardial infarction, ischaemic stroke, and the need for coronary revascularisation in people without kidney disease, but its effects in people with moderate-to-severe kidney disease are uncertain. The SHARP trial aimed to assess the efficacy and safety of the combination of simvastatin plus ezetimibe in such patients.MethodsThis randomised double-blind trial included 9270 patients with chronic kidney disease (3023 on dialysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

35
1,337
4
64

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,162 publications
(1,440 citation statements)
references
References 23 publications
35
1,337
4
64
Order By: Relevance
“…In the absence of randomized controlled clinical trials of dyslipidemia in CKD patients, these guidelines recommended following the 1992 National Cholesterol Education Program guidelines [89] for dyslipidemia goals in adults and adolescents with estimated glomerular filtration rates (eGFR) values of 15 ml./min/1.73 m 2 or greater (formerly known as CKD stages 1 to 4) and also recommended treatment in dyslipidemic adults and adolescents with eGFR values below 15 ml/min/1.73 m 2 (formerly known as stage 5 CKD) [90]. Recognizing that CKD is associated with pathological and/or clinical evidence of coronary disease before the age of 30 years and that multiple prospective studies show childhood lipid and lipoprotein profiles are predictive of future adult lipoprotein profiles with the strongest statistical correlation occurring between late childhood and the third and fourth decades of life [18,83], two expert pediatric panels published evidence-based guidelines for intensive cardiovascular risk reduction in children with CKD after the 2003 publication of the KDOQI guidelines [18,78].…”
Section: Pharmacologic Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of randomized controlled clinical trials of dyslipidemia in CKD patients, these guidelines recommended following the 1992 National Cholesterol Education Program guidelines [89] for dyslipidemia goals in adults and adolescents with estimated glomerular filtration rates (eGFR) values of 15 ml./min/1.73 m 2 or greater (formerly known as CKD stages 1 to 4) and also recommended treatment in dyslipidemic adults and adolescents with eGFR values below 15 ml/min/1.73 m 2 (formerly known as stage 5 CKD) [90]. Recognizing that CKD is associated with pathological and/or clinical evidence of coronary disease before the age of 30 years and that multiple prospective studies show childhood lipid and lipoprotein profiles are predictive of future adult lipoprotein profiles with the strongest statistical correlation occurring between late childhood and the third and fourth decades of life [18,83], two expert pediatric panels published evidence-based guidelines for intensive cardiovascular risk reduction in children with CKD after the 2003 publication of the KDOQI guidelines [18,78].…”
Section: Pharmacologic Managementmentioning
confidence: 99%
“…Since publication of the KDOQI, AHA, and NHBLI guidelines, results from more than a dozen randomized controlled trials, including three landmark trials [88][89][90], have better informed dyslipidemia management in the adult CKD population and resulted in publication of the 2013 Kidney Disease: Improving Global Outcomes (KDIGO) Clinical Practice Guideline for Lipid Management in CKD [78]. This guideline focuses on lipid management for adults and children with CKD and contains substantial changes in dyslipidemia management in adult CKD from the KDOQI guidelines including the following:…”
Section: Pharmacologic Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect on renal protection was not demonstrated in the Study of Heart and Renal Protection (SHARP) which included 2,094 (33 %) patients with diabetes [34], and the Antihypertensive and Lipid-Lowering Treatment to Prevent Heart Attack Trial (ALLHAT) which included 3,638 (36 %) patients with diabetes [35]. A meta-analysis also showed that regression of albuminuria [31] and changes in eGFR [36] were not observed in patients with diabetes treated with statins.…”
Section: Treatment Of Dyslipidemia and Diabetic Nephropathymentioning
confidence: 99%
“…There is sufficient evidence, such as SHARP [34], to show that statins reduce the risk of cardiovascular events. Considering these facts, many diabetic patients might benefit from statin treatment.…”
Section: Treatment Of Dyslipidemia and Diabetic Nephropathymentioning
confidence: 99%